Praktik Larangan Pepes Daun Pisang di Keluarga Modin Winong Pati Perspektif Hukum Adat dan Islam - Nailal Husna; Ahmad Aslamul Faizin (Universitas Cokroaminoto Yogyakarta, 2026)
This study examines the prohibition of food wrapping using banana leaves and bamboo skewers (pepes) that is specifically practiced within the Modin family in Winong District, Pati Regency, from the perspectives of customary law and Islamic law. This prohibition constitutes an internal family tradition grounded in the symbolic meaning of ngalub as a form of cultural prudence. The research employs a qualitative method with a field research design, utilizing a socio juridical approach and a normative Islamic law framework. Data were collected through interviews, observations, and library research, and subsequently analyzed using descriptive qualitative methods. The findings indicate that the pepes prohibition functions as a micro level customary legal norm that is particularistic in nature (living law) and is binding exclusively upon the Modin family. From the perspective of Islamic law, this practice falls within the domain of mu’amalat, which is essentially permissible (mubah), and may be classified as a valid urf khass. This study underscores the harmonization between customary law and Islamic law in micro level customary practices rooted in everyday symbolic meanings.